Utilizing Nature’s Potential to Improve Student Numeration Literacy Ability at SDN Sogo 2, Madiun Regency - Estuning Dewi Hapsari; Inung Diah Kurniawati; Yesi Widyasari (Information Technology and Science (ITScience), 2023)
The ability that must be developed for elementary school students is numeracy literacy. The purpose of numeracy literacy skills is that students can develop other skills in solving various problems. In fact, the numeracy skills regarding fractions and literacy in students' storytelling abilities still do not meet the minimum completeness score. So we need learning media by utilizing the natural potential around the school so that it is easy to obtain. The media used is a collage of grains and puppets from used cardboard. The study used a class action method with grade 2 students as subjects. Data collection techniques were through observation, interviews, documentation, field notes, and tests. Data is processed through reduction, description, and verification. Meanwhile, the validation used data triangulation. The results showed that there was an increase in the ability to understand fractions in each cycle. Cycle I average value of 70 and completeness of 67%. While cycle II the average value was 78 with 89% completeness. In the ability to speak cycle I, the average value was 74 with 67% completeness. While cycle II the average value is 79 with 89% completeness